Voluntary Medical Care Insurance — A Study of Non-Profit Plans in Canada - Hodgson, James (Relations industrielles / Industrial Relations, 1954)
The article reviews the book, "Voluntary Medical Care Insurance — A Study of Non-Profit Plans in Canada." Published by the Research Division, Department of National Health and Welfare, Canada (208 pages).